1978
DOI: 10.1017/s0021859600056665
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of winter wheat: 2. Soil water relations

Abstract: SummaryVolumetric soil water content and soil water potential were measured beneath a winter wheat crop during the 1975 growing season. Almost no rain fell between mid-May and mid-July and the soil dried continuously until the potential was less than – 20 bars to a depth of 80 cm. Evaporation was separated from drainage by denning an ‘effective rooting depth’ at which the hydraulic gradient was zero.Rates of water uptake per unit length of root (inflow) were calculated for the whole soil profile and for indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
46
0
5

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 26 publications
(17 reference statements)
13
46
0
5
Order By: Relevance
“…The choice of this target depth was based on the plant's active root depth, which is present from 0.30 to 0.60 m depth from the upper part of the soil. About 92% of the water uptake was extracted from the upper 0-0.60 m of the soil, and 75-80% of the root dry matter was present in this depth (Russell, 1982;Gregory et al, 1978). A plant's root depth determines the depth to which soil water can be extracted.…”
Section: Irrigation Performancementioning
confidence: 99%
“…The choice of this target depth was based on the plant's active root depth, which is present from 0.30 to 0.60 m depth from the upper part of the soil. About 92% of the water uptake was extracted from the upper 0-0.60 m of the soil, and 75-80% of the root dry matter was present in this depth (Russell, 1982;Gregory et al, 1978). A plant's root depth determines the depth to which soil water can be extracted.…”
Section: Irrigation Performancementioning
confidence: 99%
“…A relatively small biomass of roots at depth may be disproportionately important for the functioning of some ecosystems. For example, a study with winter wheat showed that 3% of the root system below 1 m supplied Ϸ20% of water uptake during a summer dry period (50). Another example is the potential importance of hydraulic lift, the passive movement of water through roots from relatively wet, deeper soil layers to relatively dry, shallower ones (51,52).…”
Section: Fig 2 Comparison Ofmentioning
confidence: 99%
“…The stored water depth was measured in volume per cent and transformed to millimetres by multiplying the water content with an effective root depth of 0.45 m. The choice of this target depth was based on the plant's active root depth, which is present from 0.30 to 0.60 m depth from the upper part of the soil as found by Russell (1982). Gregory et al (1978) found 92% of the water uptake was extracted from the upper 0-0.60 m of the soil as well as 75-80% of the root dry matter was present in this depth. Rogers and Sothers (1996) stated that the plant's root depth determines the depth to which soil water can be extracted.…”
Section: Cycle Ratiomentioning
confidence: 90%